Auto-generated site layout: an integrated approach to real-time sensing of temporary facilities in infrastructure projects - Akanmu, A.; Olatunji, O.; Love, P.; Nguyen, D.; Matthews, Jane (2015)
The use of computational algorithms is popular in method studies, especially in the aspects of knowledge that relates to construction site layout modelling. However, extant approaches in these seldom support automated tracking of construction resources and available spaces. As a result, it is often time-consuming and subjective to autogenerate site layouts. This paper describes the development and implementation of a component-level system that is capable of generating site layouts automatically. The system involves the integration of building information models, genetic algorithm and a radio frequency identification system that has the capability to report object locations in real time. System and software architectures are presented to illustrate the enabling technologies, subsystems and software that are required to facilitate the developed system. A case study is also presented to demonstrate the functionality of the developed system. The practical implication of this research is such that the reported findings builds on gaps in previous scholarly work to develop a system that models site layouts and the associated costs automatically. Findings from the study also facilitate both early signalling of pending delays and their immediate recovery protocols.